Reproductive Hormonal Evaluation Of Female Mice After Treatment With Pentoxifylline: Salema. L. Hassan ; Rajiha, A. Al- Naimi ; Saad S. Al-Dujaily - Hassan, Salema. L. (The Iraqi Journal of Veterinary Medicine, 2009)
The aim of this study was the assessment of pentoxifylline (PTX) effects on female reproductivehormones as well the body and reproductive organs. Sixty white mice with approximately same ages(eight) weeks and body weights were randomly divided into (six.) equal groups 10 mice for each group.Group 1: Received tap water along the period of experiment and considered as a control group. Animalsof group 2,3,4,5 and 6 were treated with 16 mg (PTX) / Kg B.W. daily for 2,4,6,8 and 10 weeksrespectively. Before and after treatment all animals were weighed, and blood samples were taken forfollicle stimulating hormone (FSH), lutenizing hormone (LH) and Estradiol (E2) hormones analysis.After post – Mortem examination reproductive organs were excised and weighed. The experimentrevealed that PTX administration caused increase in total body and reproductive organs weights.Concerning the biochemical tests results revealed elevation in concentration of FSH, LH and E2hormones especially significant (P<0.001) in treated groups of (8 and 10 wks duration). Compairedwith another animal groups conclusion. Administration of PTX in low dose for 10 weeks has asignificant effect on reproductive hormones. This will influence reproduction and litter size manifestedafter mating with untreated males.